Generating Ideas and Character in Learning English through Mind-mapping Activities - Wijirahayu, Suciana; Alfan, Abdul Hakim; Khadafi, Muammar (Jurnal Inovasi Pendidikan Dasar, 2023)
Academics and educators have used mapping technologies for various educational reasons. The tools are typically used in instruction to help students develop their critical and analytical thinking abilities, to help them understand how topics relate to one another, and as a means of assessment. Using multiple diagrammatic relationships instead of written or spoken descriptions is a trait of technology. Images and well-organized diagrams are easier to understand than words. The goals are to examine how mind mapping can help students write better. This study used classroom action research (CAR) as its method. It meant that the researcher and the teacher worked together on the project. This study used Elliott's model, which includes the action research's identification, reconnaissance, construction, development, and implementation steps. There were three cycles. We used an interview, a questionnaire, and a writing test. The comparison of the average score was the source to determine the outcome. We analyze five types of content: content, organization, language, and mechanics. The data showed that the mean score improved with each cycle, starting with the preliminary test or pre-test, where the mean score was 53.43 and only 7% of students passed the Standard of minimum completeness of mastery learning and ending with the third cycle, where the mean score was 81.02 and 78% of students passed the standard of a minimum of mastery learning. It implies that using a mind-mapping strategy could help pupils write better.